Regularity of flat free boundaries for a p(x)-Laplacian problem with right hand side. (November 2021) - Ferrari, Fausto; Lederman, Claudia
Abstract: We consider viscosity solutions to a one-phase free boundary problem for the p ( x ) -Laplacian with non-zero right hand side. We apply the tools developed in De Silva (2011) to prove that flat free boundaries are C 1, α . Moreover, we obtain some new results for the operator under consideration that are of independent interest.